Quantification and modification of the equilibrium dynamics and mechanics of a viral capsid lattice self-assembled as a protein nanocoating. Issue 36 (25th August 2015) - Valbuena, Alejandro; Mateu, Mauricio G.
Abstract : The equilibrium dynamics and mechanics of a viral capsid lattice that serves as a protein-based nanocoating can be quantified by AFM and chemically manipulated to increase mechanical strength and flexibility. Abstract : Self-assembling, protein-based bidimensional lattices are being developed as functionalizable, highly ordered biocoatings for multiple applications in nanotechnology and nanomedicine. Unfortunately, protein assemblies are soft materials that may be too sensitive to mechanical disruption, and their intrinsic conformational dynamism may also influence their applicability. Thus, it may be critically important to characterize, understand and manipulate the mechanical features and dynamic behavior of protein assemblies in order to improve their suitability as nanomaterials. In this study, the capsid protein of the human immunodeficiency virus was induced to self-assemble as a continuous, single layered, ordered nanocoating onto an inorganic substrate. Atomic force microscopy (AFM) was used to quantify the mechanical behavior and the equilibrium dynamics ("breathing") of this virus-based, self-assembled protein lattice in close to physiological conditions. The results uniquely provided: (i) evidence that AFM can be used to directly visualize in real time and quantify slow breathing motions leading to dynamic disorder in protein nanocoatings and viral capsid lattices; (ii) characterization of the dynamics and mechanics of a viral capsid lattice and protein-based nanocoating, including flexibility, mechanical strength and remarkable self-repair capacity after mechanical damage; (iii) proof of principle that chemical additives can modify the dynamics and mechanics of a viral capsid lattice or protein-based nanocoating, and improve their applied potential by increasing their mechanical strength and elasticity. We discuss the implications for the development of mechanically resistant and compliant biocoatings precisely organized at the nanoscale, and of novel antiviral agents acting on fundamental physical properties of viruses.